Comparative analysis of developmental and molecular correlates of developmental competence of buffalo oocytes derived from small and large follicles - PANDEY, SRITI; SOMAL, ANJALI; PARMAR, M S; GUPTA, SWATI; CHANDRA, VIKASH; KUMAR, G SAI; SHARMA, G TARU (The Indian Journal of Animal Sciences, 2017)
The present study was conducted to correlate the developmental competence of large follicle (LF, >6 mm) and small follicle (SF, <6 mm) derived buffalo oocytes in terms of morphological assessment and molecular characteristics. A pool of culture grade cumulus oocytes complexes (COCs) from both the groups separately were subjected to brilliant cresyl blue (BCB) staining. LF derived oocytes had significantly higher percentage of BCB+ve oocytes and were larger in size and maturation status was also visibly superior. Cleavage and blastocysts rate was also significantly higher in LF group than SF group. Relative mRNA expression analysis revealed that expression of GDF9 was significantly higher in LF group than SF group while expression of BMP15 increased insignificantly. Expression of GREM1, EGFR and PTGS2 was significantly higher in LF group than SF group while expression of HAS2 was insignificantly higher. Similarly, expression of GLUT1, OCT4 and IFN-ï´ in in vitro produced blastocyts was significantly higher in LF group than SF group. Thus, it can be concluded that LF derived oocytes are larger in size and express higher level of competence markers and resulted in better quality embryos. This information may be further utilized for the enhancement of developmental competence of small follicle derived oocytes.